Immunogenicity and safety of the 2015 Southern Hemisphere formulation of a split-virion inactivated quadrivalent vaccine - Cecilia Montalban; May Book Montellano; Jaime Santos; Nathalie Lavis (Taylor & Francis Group, 2018)
An inactivated split-virion quadrivalent influenza vaccine (IIV4; Fluzone® Quadrivalent; Sanofi Pasteur) has been available in the US since 2013 and in the Southern Hemisphere since 2015. Here, we describe the results of an open-label, post-licensure trial (WHO Universal Trial Number, U1111-1143-9256) to confirm the immunogenicity and safety of the Southern Hemisphere 2015 formulation of IIV4. Adults 18-60 years of age and > 60 years of age (n = 60 per age group) received a single 0.5-mL intramuscular injection of IIV4. After vaccination, hemagglutination inhibition titers for each strain in IIV4 increased by a geometric mean of at least 10-fold for younger adults and at least 9-fold for older adults. All of the younger adult participants and 98%-100% of the older adult participants had seroprotective titers for each strain. Also, at least 80% of younger adults and 78% of older adults seroconverted or had a significant increase in titer for all four vaccine strains. These post-vaccination immune responses exceeded the criteria of the Committee for Human Medicinal Products former Note for Guidance for influenza vaccines. Finally, no serious adverse events were reported, and no new safety signals were detected. These results confirmed that the Southern Hemisphere 2015 formulation of IIV4 was well tolerated, highly immunogenic, and met the criteria for influenza vaccine immunogenicity and safety.